La migración de pueblos indígenas de Bolivia y Ecuador en España - Pilar Cruz Zúñiga (Les Cahiers ALHIM)
During the final years of the twentieth century international migration from Latin America towards other regions increased significantly; this involved indigenous peoples who prior to that had been characterized by their participation in migratory movements within their own countries. This article provides a comparative overview of the transnational migration of indigenous peoples from Bolivia and Ecuador who travelled to and settled in Spain ; this offers a number of insights that might be of use to the study of contemporary cross-border migration, a topic about which there is scarce research. This text attempts to demonstrate the diversity in the composition and situation of the indigenous people and peasants involved in these migratory flows ; it emphasizes elements that help understand the specificities of this type of migration in comparison with that of other compatriots who do not identify as indigenous or peasant.